ECONOMY POTENTIAL OF BLACK SOLDIER FLY BIOCONVERSION OF CASSAVA PROCESSING WASTE: PROXIMATE COMPOSITION, FRASS CHARACTERISATION, AND INPUT SUBSTITUTION ECONOMICS IN DELTA STATE - Umeri, C.; Michael, C.; Belonwu, E.; Moseri, H.; Onwuka, H.; Lasisi, A. J. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study compares the proximate composition of fresh and dried black soldier fly larvae, characterises the nutrient profile of resultant frass biofertiliser, documents larval productivity parameters, and estimates agricultural input substitution economics under current Delta State market conditions. Proximate analyses were conducted at KAO’s Quality Assurance Laboratory, Benin City, Edo State, Nigeria, following standard AOAC methods. Fresh larvae contained 66.0% moisture, 14.0% crude protein (CP), 9.0% crude fat (EE), 3.0% crude fibre (CF), 2.0% ash, and 5.0 MJ/kg gross energy (GE). Drying to 9.0% residual moisture concentrated all nutrient parameters 2.0–4.4-fold: CP reached 32.0% DM, EE 20.0% DM, CF 7.0% DM, ash 5.0% DM, and GE 22.0 MJ/kg DM. BSF frass from cassava waste contained 3.2% total nitrogen, 2.4% total phosphorus, 2.1% total potassium, 28.4% organic carbon, and chitin at 38–52 mg/g DM, with a C:N ratio of 8.9:1. Waste mass reduction indices of 48–55% and larval biomass yields of 70–85 kg fresh biomass per tonne substrate DM were recorded. Economic analysis indicates substitution cost savings of ₦25,000–280,000 per tonne of agricultural input under 2024 Delta State market conditions, with dried larval meal as a fish meal replacer in aquaculture offering the highest economic return. The findings provide a locally grounded evidence base for advancing BSF bioconversion as a viable circular economy intervention within Nigeria’s agricultural sector.